2019
DOI: 10.1016/j.jid.2018.07.044
|View full text |Cite
|
Sign up to set email alerts
|

NEDD4 Is Involved in Inflammation Development during Keloid Formation

Abstract: Keloids mark a chronic inflammatory disease characterized by a fibroproliferative disorder of the skin. A genome-wide association study showed that single-nucleotide polymorphism rs8032158 in the neural precursor cell-expressed NEDD4 gene, which has six protein-coding transcript variants (TVs), is genetically linked to keloids. Here, we show that the high frequency of risk allele C in rs8032158 in keloid patients is associated with a selectively higher expression of TV3 of NEDD4 to activate the NF-kB pathway. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 53 publications
0
75
0
Order By: Relevance
“…Consistent with these findings, comparative analysis between GWAS data and the targets or regulatory genes of the inflammation amplifier has revealed significant relationships with human inflammatory diseases, including autoimmune diseases (Murakami et al, 2013). Indeed, the amplifier has been associated with several human diseases (Fujita et al, 2019;Lee et al, 2012). In addition, other IL-6 family members, such as LIF and IL-27, are associated with chronic obstructive pulmonary diseases (Hobbs et al, 2016;Hu et al, 2011).…”
Section: Clinical Insightsmentioning
confidence: 69%
“…Consistent with these findings, comparative analysis between GWAS data and the targets or regulatory genes of the inflammation amplifier has revealed significant relationships with human inflammatory diseases, including autoimmune diseases (Murakami et al, 2013). Indeed, the amplifier has been associated with several human diseases (Fujita et al, 2019;Lee et al, 2012). In addition, other IL-6 family members, such as LIF and IL-27, are associated with chronic obstructive pulmonary diseases (Hobbs et al, 2016;Hu et al, 2011).…”
Section: Clinical Insightsmentioning
confidence: 69%
“…They revealed a significant increase in the CC genotype in keloid patients, and showed that the rs8032158 T allele was associated with a reduced risk of keloid scarring. Also Fujita et al 16 examined 20 skin keloid specimens and found that most of them have the risk C/C genotype in rs8032158.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was found that CC genotypes cause a higher level of NEDD4 TV3 which, reportedly, acts strongly together with the RIP adapter protein to cause NF-kB activation. 16 The role of the NEDD4 TV3 signaling pathway in the aetiopathogenesis of the keloid is evaluated and its potential role as a therapeutic objective is evaluated 16 . Fujita et al 16 studied the immunohistochemical expression of NEDD4 in different samples of normal and human keloid skin using an anti-NEDD4 antibody that identifies all TVs types.…”
Section: Dovepressmentioning
confidence: 99%
See 2 more Smart Citations